Inherent single‐cell bioelectrical parameters of thousands of neutrophils, eosinophils and basophils derived from impedance flow cytometry. Issue 8 (21st April 2022) - Wang, Minruihong; Zhang, Jie; Tan, Huiwen; Chen, Deyong; Lei, Ying; Li, Yueying; Wang, Junbo; Chen, Jian
Abstract: Single‐cell bioelectrical properties are commonly used for blood cell phenotyping in a label‐free manner. However, previously reported inherent single‐cell bioelectrical parameters (e.g., diameter D c, specific membrane capacitance C sm and cytoplasmic conductivity σ cy ) of neutrophils, eosinophils and basophils were obtained from only tens of individual cells with limited statistical significance. In this study, granulocytes were separated into neutrophils, eosinophils and basophils based on fluorescent flow cytometry, which were further aspirated through a constriction‐microchannel impedance flow cytometry for electrical property characterization. Based on this microfluidic impedance flow cytometry, single‐cell values of D c, C sm and σ cy were measured as 10.25 ± 0.66 μm, 2.17 ± 0.30 μF/cm 2, and 0.37 ± 0.05 S/m for neutrophils ( n cell  = 9442); 9.73 ± 0.51 μm, 2.07 ± 0.19 μF/cm 2, and 0.30 ± 0.04 S/m for eosinophils ( n cell  = 2982); 9.75 ± 0.49 μm, 2.06 ± 0.17 μF/cm 2, and 0.31 ± 0.04 S/m for basophils ( n cell  = 5377). Based on these inherent single‐cell bioelectrical parameters, neural pattern recognition was conducted, producing classification rates of 80.8% (neutrophil vs. eosinophil), 77.7% (neutrophil vs. basophil) and 59.3% (neutrophil vs. basophil). These results indicate that as inherent single‐cell bioelectrical parameters, D c, C sm and σ cy can be used to classify neutrophils from eosinophils or basophils to some extent while they cannot be used to effectively distinguish eosinophils from basophils.